An FFT-Based DC Offset Compensation and I/Q Imbalance Correction Algorithm for Bioradar Sensors - Tian, Fuze; Zhu, Lixian; Shi, Qiuxia; Jin, Xiaokun; Cai, Ran; Dong, Qunxi; Zhao, Qinglin; Hu, Bin (IEEE transactions on microwave theory and techniques, 2024)
The challenge of noncontact presentation of human cardiopulmonary activity using a bioradar sensor is to linearly demodulate the Doppler cardiopulmonary diagram (DCD) signal from baseband signals. Arctangent demodulation can perform linear phase demodulation to obtain the DCD signal. However, the high-order harmonics and intermodulation terms (ITs) caused by the time-varying direct current (dc) offset and in-phase and quadrature-phase (I/Q) imbalance in the baseband signals significantly degrade the signal-to-noise ratio (SNR) of the Doppler heartbeat diagram (DHD) signal. In this work, a fast Fourier transform (FFT)-based algorithm is proposed to simultaneously perform time-varying dc offset compensation and I/Q imbalance correction without the need for an auxiliary device to improve the accuracy of the arctangent demodulation. The obtained results show that the SNRs of the algorithm-processed DHD signals are increased from 30.08 ± 2.41 to 68.88 ± 10.57 dB. In addition, the root mean square errors (RMSEs) of the C-C intervals of the DHD signals for eight subjects with respect to the J-J intervals of the ballistocardiogram (BCG) signals are 17.79 ± 2.72 ms (2.80% ± 0.43%), suggesting a promising potential of the DHD signal for noncontact biomedical applications.